Menata Bahasa dalam Laporan Ilmiah: Cermin Ketajaman Bernalar - da Costa, Romilda Arivina (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2024)
Writing is one of the expressive and productive language skills. To achieve these skills, especially those related to scientific writing, including scientific reports or practicum reports, requires intensive learning and training. Mastery of writing theory and knowledge can be obtained through learning activities, while training activities contain the concept of getting used to writing behavior. In community service activities that carry the theme Organizing Language in Scientific Reports: A Mirror of Reasoning Acumen, this community service activity presents the theory and knowledge of writing along with simple strategies to start writing practicum reports, which has been a concern of SMK Negeri 10 Seram Barat for final year students who have completed practice in agencies that collaborate with the school. The implementation of this community service activity began with a quiz on Indonesian word equivalents for certain terms that are widely used in society, followed by information on various supporting references, such as KBBI, Thesaurus, and EYD 2022, then a brief description of writing as a reasoning process, and ended with an example of describing facts. The counseling has enlightened the students of SMA Negeri 10 Seram Barat to develop writing as a fun habit, and through writing, they are expected to recognize their abilities and potential.